Process of Care and Prescribing Practices for Hypertension in Public and Private Primary Care Clinics in Malaysia - Tong, S.F.; Khoo, Ee Ming; Nordin, S.; Teng, C.L.; Lee, V.K.M.; Zailinawati, A.H.; Chen, W.S.; Mimi, O. (SAGE Publications, 2012)
This study aimed to compare the process of care and the choice of antihypertensive medications used in both public and private primary care clinics in Malaysia. A cross-sectional survey was completed in 2008 on randomly selected 100 public health clinics and 114 private primary care clinics in Malaysia. A total of 4076 patient records, 3753 (92.1) from public clinics and 323 (7.9) from private clinics were analyzed. Less than 80 of the records documented the recommended clinical and laboratory assessments. The rates of documentation for smoking status, family history of premature death, retinal assessment, and urine albumin tests were lower in public clinics. Overall, 21 of the prescription practices were less than optimal. The process of care and the use of antihypertensive medications were not satisfactory in both settings.